Holt-Oram Syndrome in Adult Presenting with Heart Failure: A Rare Presentation. (23rd March 2014) - Kumar, Rupesh; Mahapatra, Subhendu Sekhar; Datta, Monalisa; Hoque, Amanul; Datta, Swarnendu; Ghosh, Soumyajit; Datta, Santanu; Bhattacharjee, Subhankar
Abstract : Holt-Oram syndrome is a rare inherited disorder involving the hands, arms, and the heart. The defects involve carpal bones of the wrist and the thumb and the associated cardiac anomalies like atrial or ventricular septal defects. Congenital cardiac and upper-limb malformations frequently occur together and are classified as heart-hand syndromes. The most common amongst the heart-hand disorders is the Holt-Oram syndrome, which is characterized by septal defects of the heart and preaxial radial ray abnormalities. Its incidence is one in 100, 000 live births. Approximately three out of four patients have some cardiac abnormality with common associations being either an atrial septal defect or ventricular septal defect. Herein, we report a rare sporadic case of Holt-Oram syndrome with atrial septal defect with symptoms of heart failure in a forty-five-year-old lady who underwent emergency cardiac surgery for the symptoms.